Dielectric, ferroelectric and piezoelectric properties of MnO2-doped Pb(Yb1/2Nb1/2)O3-Pb(Zr, Ti)O3 ceramics. Issue 7 (May 2018) - Luo, Xiao; Zeng, Jiangtao; Shi, Xue; Zheng, Liaoying; Zhao, Kunyu; Man, Zhenyong; Li, Guorong
Abstract: 0–0.8 wt% MnO2 doped 0.33Pb(Yb1/2 Nb1/2 )O3 –0.18PbZrO3 –0.49PbTiO3 (PYN-PZT) ceramics were prepared by solid state reaction method and the influence of MnO2 modification on their crystal structure, ferroelectric and piezoelectric properties of PYN-PZT ceramics was investigated. It was found that small amount of MnO2 modification did not change the crystal structure of the PYN-PZT ceramics. Whereas a large internal bias was observed which indicates the existence of defect dipoles. Piezoelectric constant ( d 33 ) decreased while mechanical quality factor ( Q m ) increased with the increase of MnO2 content due to the domain wall pinning effect. The influence of sintering atmosphere on the properties of Mn doped PYN-PZT ceramics was also investigated. For their high Curie temperature T c, good piezoelectric properties and high Q m ，MnO2 doped PYN-PZT ceramics may be suggested as good candidates for high power piezoelectric applications.